CELL RENEWAL IN THE AREAS OF INTESTINAL METAPLASIA OF THE GASTRIC MUCOSA IN PRECANCEROUS CONDITIONS - Vernigorodskiy, S.V.; Degtyaryova, L.V. (World of Medicine and Biology, 2012)
The high proliferative activity of the epithelium (Ki-67) and the appearance of p53 in the areas of incomplete intestinal metaplasia were established on the basis of immunohistochemical analysis of gastrobiopsies of patients with chronic atrophic gastritis, which allows to emphasize the atypical ("hyperproliferative") type of intestinal metaplasia of the gastric mucosa. The further using of immunohistochemical markers Ki-67 and p53 for screening patients with high risk of neoplastic transformation of gastric mucosa was proposed.
Keywords: cell renewal; intestinal metaplasia; gastric mucosa